Implementation of No-Smoking Area Policy at the Cingcin Village Office, Bandung District - Nyimas Riah Afrilianti; M. Ridwan Caesar (GoResearch - Research & Publishing House, 2024)
Smoking, as a personal right, poses challenges in balancing individual freedom with the rights of others not to be exposed to cigarette smoke. The health impacts of smoking, including lung disease, reproductive dysfunction, pregnancy disorders, strokes, and heart attacks, are widely known. The government implemented a smoke-free area policy, but Cingcin Village experienced implementation obstacles such as a lack of socialization, warnings, inconsistent attitudes, and bureaucratic ambiguity. In the context of Edwards III's theory (in Subianto 2020) factors such as communication, resources, disposition, and bureaucracy play an important role in policy implementation. Therefore, using qualitative methods, researchers chose this theory to study the implementation of the No Smoking Zone (KTR) policy in Cingcin Village. Cingcin Village has implemented the No Smoking Zone (KTR) policy, although the implementation is still not perfect. The most prominent obstacle is the lack of funds to support facilities for the No Smoking Zone (KTR) policy and the lack of socialization and understanding from Cingcin Village officials themselves. An effective solution is to increase socialization through special programs and media such as videos. It is hoped that this can increase understanding of the No-Smoking Zone rules in Cingcin Village.